Research of STATCOM Impact on Wind Farm LVRT and Protection - YANG Bai-jie; CHAO Qin; YUAN Tie-jiang; YI Hai-dong (Institute of Advanced Engineering and Science, 2012)
Because of the wind turbine which possesses low voltage ride through (LVRT) capability can keep on working during the system fault, greatly reduce the adverse effects of power grid and ensure the relay protection reliability. However, the asynchronous wind turbine which widely used in home and abroad doesn’t have enough LVRT capability. So this paper proposes a method to enhance the LVRT capability of fixed speed induction generator (FSIG) based on wind farm using static synchronous compensator (STATCOM). And this paper establishes the simulation model of asynchronous wind generator wind farm and STATCOM in Matlab/Simulink software; the research results show that the STATCOM device can improve asynchronous wind farm LVRT capability. Then analysis the asynchronous wind generator which possess LVRT ability characteristics and the time of the action protection relations．According to the current wind farm system protection configuration, studying the asynchronous wind farm which with STATCOM device effect on protection configuration of system and the existing problems. At last, putting forward some reasonable measures of improving LVRT cooperate with relay protection characteristics and minimizing probability of wind power units take off the grid． DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1650